DESIGN SOLUTIONS FOR REDUCTION OF VOLUMETRIC LOSS OF OPERATING FLUID IN GEAR-TYPE FLUID MAKEUP PUMP OF SWASH PLATE TYPE FLUID MACHINES (Modern Problems of Metallurgy, 2019)
The research was carried out on the operational reliability of fluid makeup pumps, the results of which concluded that it is necessary to develop design solutions for reduction of volumetric loss of operating fluid in gear-type fluid makeup pump of swash plate type fluid machines. The purpose of research is to increase operational durability of fluid makeup pump of swash plate type fluid machines by developing design solutions for reduction of volumetric loss in its pumping unit. A method is proposed for compensation of the end clearance using an end clearance compensation plate, which consists of a functional surface and an elastic-damping element, in which channels and chambers of hydrostatic lift are additionally located. The analysis of the forces that act on the end clearance compensation plate is made and their optimal ratio is substantiated, which ensures the value of the end clearance, that causes the minimum volumetric loss of the operating fluid in the pumping unit of the fluid makeup pump and increases its operational durability.
Keywords: volumetric loss; fluid makeup pump; durability